1997
DOI: 10.1021/jp963800y
|View full text |Cite
|
Sign up to set email alerts
|

Photofragmentation of Acetyl Cyanide at 193 nm

Abstract: The photodissociation of gaseous acetyl cyanide has been examined following excitation at 193 nm. CN X2Σ+ photofragments were probed via laser fluorescence excitation to determine their rotational, vibrational, and translational energy distributions. CN was produced in v‘‘ = 0 and 1 with mean rotational energy (13.5 ± 2) kJ mol-1, and v‘‘ = 2 with mean rotational energy (10 ± 4) kJ mol-1. Mean translational energies of the CN fragments were (32 ± 10) kJ mol-1. Ab initio electronic structure theory has been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
76
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 29 publications
(47 reference statements)
14
76
0
Order By: Relevance
“…Further, the calculated value of the dissociation energy for COCN • → CO + CN • is found to be 35.8 kcal/mol (DFT) (table 2) which is close to the estimated experimental value of 35.9 kcal/mol [1]. Horwitz et al [8], however, reported a much lower value of 30.1 kcal/mol from RHF ab initio calculations using G2 theory.…”
Section: Decomposition Processsupporting
confidence: 79%
See 3 more Smart Citations
“…Further, the calculated value of the dissociation energy for COCN • → CO + CN • is found to be 35.8 kcal/mol (DFT) (table 2) which is close to the estimated experimental value of 35.9 kcal/mol [1]. Horwitz et al [8], however, reported a much lower value of 30.1 kcal/mol from RHF ab initio calculations using G2 theory.…”
Section: Decomposition Processsupporting
confidence: 79%
“…Present calculations further tend to rationalize some of the findings of Furlan et al [1] on photodecomposition in CO(CN) 2 and Horwitz et al [8] in CH 3 COCN by 193 nm radiation. Since the photon energy of 193 nm radiation is 148.2 kcal/mol, the available energy in photodecomposition experiment of Furlan et al [1] in a sequential reaction is 51.0 kcal/mol.…”
Section: Decomposition Processsupporting
confidence: 78%
See 2 more Smart Citations
“…[128][129][130][131] In particular, one usually expects that most of the potential energy released along the reaction coordinate after passing the barrier is converted to relative translational energy of the photofragments, and that the translational energy distribution is rather insensitive to the total available energy. 108,[132][133][134][135] In contrast, reactions without an exit channel barrier typically have an asymmetric bell-shaped translational energy distribution with its maximum somewhat away from zero translational energy. 128,130 It can be seen from Also, from the 6S-MC-QDPT energies in Fig.…”
Section: Ivb Geometries At Avoided Crossingsmentioning
confidence: 99%